Banking competition, good or bad?: The case of promoting micro and small enterprise finance in Kazakhstan - Schäfer, Dorothea (Applied economics, 2010)
Competition is claimed to be beneficial in development projects promoting micro and small enterprise finance although there are still doubts as to whether these loans can be developed into a profitable business. Our research sheds new light on the question of how many MSE banking units should optimally be created and supported in a certain region. We employ a unique data set from the European Bank for Reconstruction and Development for Kazakhstan, and investigate which strategy contributes more to the overall success of the programme: a strategy of setting up several competing banks or a strategy of establishing regional monopolies. 'Competition is the most important principle on which our strategy is based. As in any other market, effective competition provides incentives for banks to offer market-based and demand-oriented financial services.